2018
DOI: 10.1021/acs.est.8b00596
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Transfer and Transformation of CeO2 Nanoparticles along a Terrestrial Food Chain: Influence of Exposure Routes

Abstract: The trophic transfer and transformation of CeO nanoparticles (NPs) through a simulated terrestrial food chain were investigated using a radiotracer technique and X-ray absorption near edge structure (XANES). Radioactive CeO NPs were applied to head lettuce ( Lactuca sativa), treated via root exposure in its potting soil (5.5 or 11 mg/plant) for 30 days or foliar exposure (7.2 mg/plant, with half of the leaves treated and the other half not) for 7 days. Subsequently, two groups of land snails ( Achatina fulica)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 48 publications
2
31
1
Order By: Relevance
“…Next, the uniformly pregrown seedlings were selected and exposed to Ag + , AgNPs, TiO 2 NPs, the mixture of AgNPs and TiO 2 NPs, or the Hoagland solution alone (as the negative control) via the roots for 28 days. 19 Each treatment had 30 seedlings/replicates. All of the tubes containing a seedling and exposure medium were covered with aluminum foil to minimize the impact of light-induced transformations of AgNPs and TiO 2 NPs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the uniformly pregrown seedlings were selected and exposed to Ag + , AgNPs, TiO 2 NPs, the mixture of AgNPs and TiO 2 NPs, or the Hoagland solution alone (as the negative control) via the roots for 28 days. 19 Each treatment had 30 seedlings/replicates. All of the tubes containing a seedling and exposure medium were covered with aluminum foil to minimize the impact of light-induced transformations of AgNPs and TiO 2 NPs.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the transfer of AuNPs from tobacco to tobacco hornworm occurred with trophic transfer factors of 6.2–11.6, 17 while CeO 2 NPs were not magnified at all from lettuce to snail (trophic transfer factor = 0.037). 19 However, in none of the mentioned publications, the impact of trophic transfer of NPs on the behavioral alterations of the consumers was investigated. This information is valuable for assessing their possible risks to the environment and ecosystem health.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al ( 2013 ) reported that the Solanum lycopersicum L. growth was smaller when plants were spiked with CeO 2 -ENPs, and, consequently, the biomass production decreased, but the ROS content in root was improved. In contrast, Xie et al ( 2019 ) and Ma et al ( 2018 ) found that the presence of CeO 2 -ENPs in Phaseolus vulgaris L. and Brassica rapa L. plants, respectively, did not affect their growth, but in the case of Brassica rapa L., the chlorophyll content increased.…”
Section: Resultsmentioning
confidence: 89%
“…In another study where Ce-ENPs were added (1000 mg kg −1 dry soil) in soil pots containing lettuce ( Lactuca sativa ) and snails ( Achatina fulica ), a trophic transfer of Ce-ENPs from the plant toward the snails was demonstrated. It shows that the potential risk of transferring Ce to humans through the food chain is less obvious (Ma et al, 2018 ). By contrast, Chae et al ( 2016 ) studied a trophic transfer of NPs from Saccharomyces cerevisiae yeast to Armadillidium vulgare through the Folsomia candida (collembola).…”
Section: Resultsmentioning
confidence: 99%
“…Trophic transfer studies with CeO 2 NPs have shown that transfer and biomagnification of Ce occurs within the studied food chains [135,136,137].…”
Section: Soybean Interactions With Enmsmentioning
confidence: 99%